Perturbations in amino acid metabolism in reserpine-treated zebrafish brain detected via 1H NMR-based metabolomics - Zakaria, Fauziahanim; Akhtar, Muhammad Tayyab; Wan Ibrahim, Wan Norhamidah; Abu Bakar, Noraini; Muhamad, Azira; Shohaimi, Shamarina; Maulidiani, Maulidiani; Ahmad, Hafandi; Ismail, Intan Safinar; Shaari, Khozirah (Mary Ann Liebert, Inc., 2021)
Depression is a complex and disabling psychiatric disorder, which is expected to be a leading cause for disability by 2030. According to World Health Organization, about 350 million people are suffering with mental health disorders around the globe, especially depression. However, the mechanisms involved in stress-induced depression have not been fully elucidated. In this study, a stress-like state was pharmacologically induced in zebrafish using reserpine, a drug widely used to mediate depression in experimental animal models. Zebrafish received single intraperitoneal (i.p.) injections of 20, 40, and 80 mg/kg body weight reserpine doses and were subjected to open-field test at 2, 24, 48, 72, and 96 h after the treatment. Along with observed changes in behavior and measurement of cortisol levels, the fish were further examined for perturbations in their brain metabolites by 1H nuclear magnetic resonance (NMR)-based metabolomics. We found a significant increase in freezing duration, whereas total distance travelled was decreased 24 h after single intraperitoneal injection of reserpine. Cortisol level was also found to be higher after 48 h of reserpine treatment. The 1H NMR data showed that the levels of metabolites such as glutamate, glutamine, histamine, valine, leucine and histidine, lactate, l-fucose, betaine and γ-amino butyric acid (GABA), β-hydroxyisovalerate, and glutathione were significantly decreased in the reserpine-treated group. This study provided some insights into the molecular nature of stress that could contribute toward a better understanding of depression disorder.